2020
DOI: 10.4081/jphr.2020.1868
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 Pandemic's Impact on Eating Habits in Saudi Arabia

Abstract: Background: COVID-19 virus has been reported as a pandemic in March 2020 by the WHO. Having a balanced and healthy diet routine can help boost the immune system, which is essential in fighting viruses. Public Health officials enforced lockdown for residents resulting in dietary habits change to combat sudden changes. Design and Methods: A cross-sectional study was conducted through an online survey to describe the impact of the COVID-19 pandemic on the eating habits, quality and quantity of food intake among a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
91
4
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(138 citation statements)
references
References 45 publications
17
91
4
4
Order By: Relevance
“…Our results also show that around 50% of the sample reported usually or often eating sugary food more during than before COVID-19. This is compatible with findings in other studies showing that self-quarantine adversely affected dietary intake and habits [ 39 , 40 ], increased emotional eating [ 42 ], and altered normal lifestyle behaviors [ 7 ]. This may be caused by the negative impacts of quarantine reducing the motivation to maintain healthy habits [ 43 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results also show that around 50% of the sample reported usually or often eating sugary food more during than before COVID-19. This is compatible with findings in other studies showing that self-quarantine adversely affected dietary intake and habits [ 39 , 40 ], increased emotional eating [ 42 ], and altered normal lifestyle behaviors [ 7 ]. This may be caused by the negative impacts of quarantine reducing the motivation to maintain healthy habits [ 43 ].…”
Section: Discussionsupporting
confidence: 92%
“…The weight loss reported in the present study could have been partially influenced by reduced reported fast food intake. The lockdown in Saudi Arabia and other gulf countries like Kuwait forced restaurants, malls, and delivery applications to limit their hours, decreasing fast food and restaurant meals while increasing regular home-cooked meals [ 39 , 40 ]. Approximately 57% of the women in the weight-loss group decreased their total food intake and daily snacks.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 1489 studies were identified through databases and reference searching and after removal of 642 duplicates, 847 studies were screened. Hence, 32 studies [ [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] ] (all cross-sectional) were included in this systematic review. Characteristics of the 32 cross-sectional included studies can be found in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Changes in fast-food consumption were reported in eight studies [ 19 , 20 , 24 , 25 , 28 , 34 , 35 , 46 ] and changes in ordered food were examined in three studies [ 15 , 18 , 23 ], whereas relevant results are summarized in Table 3 , Table 4 respectively. In four studies, more than 50% of the participants’ fast-food consumption remained unchanged during lockdown [ 24 , 28 , 34 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation